(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ficus benjamina is a popular house plant in temperate regions due to its graceful growth and adaptability to a wide range of environmental conditions. It thrives in full sun but can also survive in partial shade. In the summer, it needs a moderate quantity of water, while in the winter, it needs just enough to prevent drying out. Research has demonstrated that Ficus benjamina may efficiently remove gaseous formaldehyde from the air in a home. Although the fruit is edible, it is not why the plant is often cultivated. The leaves are very sensitive to subtle changes in illumination. Inflammation, which may be caused by many different things and is currently the biggest health problem, was the driving force for the initiative. The fig tree, or Ficus benjamina, is a valuable medicinal plant. The Ficus benjamina voucher specimen SG/KN/3210 was placed in our department after being collected from the area surrounding alwar city and validated by Dr. S. N. Dwivedi, Professor & Head of the Department of Botany at Janata PG College, APS, University in Rewa, Madhya Pradesh. The various extract obtained after extraction were subjected for phytochemical screening to determine the presence of following various phytochemical present in the extracts. Microscopy and powder microscopy examinations of the stem of Ficus benjamina have shown that it is a dicot stem with an epidermis, hypodermis, pericycle, conjoint and collateral vascular bundle, medullary rays, and a pith. The current investigation aimed to determine whether or not an herbal gel comprising extract from the fig tree (Ficus benjamina) have anti-inflammatory properties.